Implementation of Vygotsky's Constructivism Theory Through the Project Based Learning Model of PAK Teachers Impacts Problem Solving of Grade XI Students at SMA Negeri 1 Kauditan - Ranting, Hermin; Rumetor, Jelty Juriaty; Liud, Yahya Herman; Rakim, Ristan; Kambong, Hizkia Joel; Nendissa, Julio Eleazer; Wohon, Frimsi (PT Inovasi Pratama Internasional, 2025)
The era of education that increasingly demands an increase in the quality of human resources (HR) has positioned teachers as an important component in the learning process. The application of learning methods that are relevant to the demands of the times is needed to encourage the development of students' increasingly complex problem-solving skills. Christian Religious Education (PAK) teachers are expected to be able to present a learning environment that is conducive to the development of students' abilities through a contextual and project-based approach. Project Based Learning (PjBL) is one of the learning models that aims to provide real project-based learning experiences to students. This model is based on the principles of Vygotsky's constructivism, which emphasizes the importance of social interaction and collaboration in learning. In the context of PAK learning, project based learning helps students develop critical, analytical, and creative thinking skills, as well as problem-solving abilities. This study uses a descriptive qualitative approach to analyze the impact of implementing the project based learning model on improving the problem-solving abilities of grade XI students at SMA Negeri I Kauditan. Data collected through observations, interviews, and questionnaires involving students and Christian Religious Education (PAK) teachers show that project based learning has proven effective in developing students' critical and analytical thinking skills. Students feel more confident in facing challenges, more collaborative in working in groups, and more disciplined in completing tasks. Teacher evaluations also confirm that the process of working on a project is as important as the end result, because it can describe the development of students' problem-solving skills as a whole.